Turning Local Fight Global: Strategi Advokasi Transnasional Environmental Justice Foundation dalam Upaya Memberantas Praktik “Saiko” di Ghana - Khanid Rachmadia Nova Putri; Reni Windiani; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2022)
Fisheries is an important sector as a source of nutrition, income, and livelihood support for Ghanaian citizens. However, the Ghanaian fishing sector tends to be threatened by a number of problems which are mainly caused by illegal, unreported, and unregulated (IUU) fishing activities, in particular the practice commonly known as “Saiko” (transshipment). In response to this, a local Ghanaian non-governmental organization, Hen Mpoano, have attempted to advocate for the importance of eradicating Saiko practices in order to ensure the sustainability of the Ghanaian fisheries sector and formed a transnational network with the Environmental Justice Foundation (EJF) as an international non- governmental organization engaged in the humanitarian and environmental fields to advocate for the issue of Saiko practices in the global realm so that it can put pressure on the Ghanaian government to prioritize efforts to eradicate Saiko practices in its government agenda. This study aims to provide an explanation regarding the transnational advocacy strategies carried out by EJF using the conceptual framework of the Transnational Advocacy Network introduced by Keck and Sikkink. The findings of this study reveal that the transnational advocacy efforts carried out by EJF are carried out by implementing information politics, symbolic politics, leverage politics, and accountability politics.